The Impact of Discipline and Integrity on The Performance of Telkom Employees in The South Surabaya Region - Okky Nur Susanto; Slamet Riyadi; Abdul Halik (Economic and Bussiness Faculty, Dr Soetomo University, 2023)
Discipline and integrity possessed by employees is a reflection of the company's performance, both of which will be able to affect employee performance. Maintaining the discipline and integrity of employees is one of the important functions of operational human resource management because the better the level of discipline and integrity of employees, it will simultaneously affect the company's performance. This study aims to determine the impact of discipline and integrity on employee performance. Discipline is tested through example, waskat (attached supervision), firmness. Integrity is tested through honesty, consistency, commitment. Performance is tested through the quality of work, responsibility, cooperation. The research method is quantitative with a sample taken of 110 Telkom employees in the South Surabaya Region. The data analysis technique uses the Structural Equation Modeling (SEM) method using IBM SPSS Statistics and AMOS version 24 software. The results of this study indicate that discipline and integrity have a significant influence on the performance of Telkom employees in the South Surabaya Region